Development of a Differentiated Project-Based e-Worksheet Using the STEM Approach to Foster 21st-Century Skills of Students on the Topic of Global Warming - Siti Aisyah; Agus Suyatna; Viyanti Viyanti (Jurnal Ilmiah Pendidikan Fisika, 2025)
Learning about global warming in schools is often theoretical and lacks meaningful, real-world problem-solving activities that engage students. As a result, students’ 21st-century skills, such as critical thinking, collaboration, and digital literacy, are not optimally developed due to the lack of innovative, differentiated learning media, including project-based e-worksheets that utilize the STEM approach. This study aims to develop a differentiated, project-based student worksheet utilizing a STEM approach that is valid, practical, and effective in training students' 21st-century skills, particularly in the context of global warming and the greenhouse effect. The research method used is development research, with the ADDIE design, consisting of the stages Analyze, Design, Development, Implementation, and Evaluation. This research was conducted in three meetings at SMAN 1 Katibung. Data analysis techniques include percentage analysis for validity and practicality scores, as well as statistical analysis to determine effectiveness. The results show that the differentiated worksheet developed has high validity in terms of content, construct, language, and design, with a score of 87.08%. In terms of practicality, it demonstrates high levels of readability, attractiveness, and feasibility, scoring 88.3%, categorized as very practical. Furthermore, the e-Worksheet has been proven effective in fostering students’ 21st-century skills, as evidenced by N-Gain scores of 0.61 (moderate improvement) for critical thinking and 0.56 (moderate) for creative thinking. The application of differentiated learning in the experimental class showed a moderate effect size of 0.469 for critical thinking skills and 0.294 for creative thinking skills. These findings indicate that the differentiated project-based e-worksheet can accommodate students’ varying needs, including their initial abilities and learning styles, and is necessary to support the development of 21st-century skills.